BACTERIAL HUNGER GAMES: SMALL ALARMONE SYNTHETASES IN MRSA VS. MSSA - Mussa, Ali Abdulridha; Al-Mathkhury, Harith Jabbar Fahad (Eastern Ukrainian Medical Journal, 2024)
Introduction. Staphylococcus aureus is a significant global human pathogen associated with opportunistic infections. The stringent response in bacteria triggers the synthesis of alarmones (p(ppGpp)) upon encountering stress conditions like starvation, impacting the bacterial transcriptome. S. aureus synthesizes these alarmones using either the Rel enzyme (RelA/SpoT homolog) or the small alarmone synthetases RelP and RelQ. Aim. This investigation aimed to (1) highlight the impact of starvation on biofilm intensity, cell count, and matrix composition (protein, polysaccharide, and DNA) in both MRSA and MSSA isolates and (2) analyze the expression levels of relP and relQ genes under normal and starved conditions in both MRSA and MSSA isolates. Methods: S. aureus isolates were obtained from patients attending hospitals in Baghdad. Methicillin resistance was determined using the cefoxitin disc diffusion method. PCR confirmed the presence of relP and relQ genes in all isolates. Additionally, 16SrRNA gene segments from 10 isolates were amplified for sequencing. Biofilm intensity, matrix composition, and cell count were measured for 10 isolates (5 MRSA and 5 MSSA) under normal and starvation conditions. Finally, relP and relQ gene expression was compared under both conditions. Results: Methicillin resistance was detected in 94% of S. aureus isolates. relP and relQ genes were present in 100% and 98.7% of isolates, respectively. Biofilm thickness and cell count significantly decreased (P = 0.0020) after starvation and with treatment involving proteinase K, DNase, and sodium periodate (P < 0.0001). relP and relQ genes displayed upregulation after starvation. Conclusion: Starvation significantly reduced biofilm formation and altered its composition, suggesting the potential involvement of the stringent response in biofilm regulation; both relP and relQ were upregulated in both MRSA and MSSA.